The Role of Religiosity in Functional Value, Trust Engagement, and Intentions to Reuse - Rosyad , Sabilar; wahyudi, Lilik; Haryanto, Budhi; Sugiarto, Catur (International Journal of Accounting and Economics Studies, 2025)
Given the growing interest in alternative consumption channels, this paper discusses a conceptual framework for examining the relationship ‎between online consumers' repeated online perceived value of recycled products and their repurchase intentions from recycling platforms. ‎This study aims to test the conceptual model and validate the model with one type of product. Based on cognitive, social, and sub-cultural ‎theory, trust (seller and platform) and involvement in consumer-to-consumer online marketplaces are hypothesized to mediate consumers' ‎perceived functional value and their intention to reuse, as well as adding the moderating variable Religiousity. For the religiosity moderation ‎variable, it can be seen that the religiosity moderation variable moderates the functional value of trust(Seller and platform). This study ‎highlights the implications of trust and engagement and how these factors influence consumer intentions to reuse C2C online recycling mar-‎marketplace platforms‎.